A Study of Bone Mineral Density in Diabetes Mellitus in Iranian Women - Zh Maghbooli; A Hossein-nezhad; M Khoshniat; H Adibi; N Mohammadzadeh; B Larijani (Tehran University of Medical Sciences, 2007)
Background: In view of the current high prevalence of diabetes mellitus (DM) and osteoporosis, today there is great inter¬est in studying the possible association between these two disorders. The aim of this study was to determine the association be¬tween type-2 DM, and Bone mineral density (BMD) in Iranian women. Methods: BMD was determined in the femoral neck and at the L2-L4 level (DEXA) 0f 518 women aged 40-80 years old, re¬ferred to bone densitometry unit of Endocrinology and Metabolism Research Center of Tehran University of Medical Sci¬ences (146 patients with type 2 diabetes and 372 normal controls). Results: In diabetics patients, BMD values at the vertebral site were higher than non-diabetic patients but the difference was only significant in postmenopausal subgroup (P= 0.045). Besides, BMD values at the hip site were higher when com¬pared with non-diabetes group, but the difference was not significant. Frequency of osteoporosis risk factors (tea consump¬tion, sunlight exposure, late menarche, low physical activity, smoking habits, family history of osteoporosis and inadequate cal¬cium intake) were not significantly different between diabetic and non-diabetic women , but prevalence of early meno¬pause was higher in diabetic women (P= 0.046). Prevalence of osteoporosis in premenopausal and postmenopausal was 7% and 41.6% in diabetic and 15% and 36.8% in non-diabetic women, respectively. Prevalence of osteoporosis and osteopenia was not significantly different in diabetic and non-diabetic groups. Conclusion: The present results demonstrate that there is not clear association between BMD and type 2 diabetes mellitus.